Cost analysis of acute care resource utilization among individuals with sickle cell disease in a middle-income country - Clarisse Lobo; Patricia Moura; Delaine Fidlarczyk; Jane Duran; Roberto Barbosa; Thais Oliveira; Emilia Matos do Nascimento; Nickhill Bhakta; Jane S. Hankins (BMC, 2022)
Abstract Background The costs associated with the treatment of sickle cell disease (SCD) are understudied in low and middle-income countries (LMIC). We evaluated the cost of treating SCD-related acute complications and the potential cost-savings of hydroxyurea in a specialized hematology center in Brazil. Methods The costs (US dollars) of emergency department (ED) and hospitalizations from SCD-related complications between 01.01.2018 and 06.30.2018 were ascertained using absorption and micro-costing approaches. The reasons for acute hospital visits were grouped as: 1) vaso-occlusive (VOC) pain, 2) infection, 3) anemia exacerbation, and 4) chronic organ damage complications. Hydroxyurea adherence was estimated by medication possession ratio (MPR) during the study period. Results In total, 1144 patients, median age 17 years (range 0-70), 903 (78.9%) with HbSS/HbSβ0-thalassemia, 441 (38.5%) prescribed hydroxyurea, visited the ED, of whom 381 (33%) were admitted. VOC accounted for 64% of all ED visits and 60% of all admissions. Anemia exacerbation was the most expensive reason for ED visit ($321.87/visit), while chronic organ damage carried the highest admission cost ($2176.40/visit). Compared with other genotypes, individuals with HbSS/HbSβ0-thalassemia were admitted more often (79% versus 21%, p < 0.0001), and their admission costs were higher ($1677.18 versus $1224.47/visit, p = 0.0001). Antibiotics and analgesics accounted for 43% and 42% of the total ED costs, respectively, while housing accounted for 46% of the total admission costs. Costs of ED visits not resulting in admissions were lower among HbSS/HbSβ0-thalassemia individuals with hydroxyurea MPR ≥65% compared with visits by patients with MPR <65% ($98.16/visit versus $182.46/visit, p = 0.0007). No difference in admission costs were observed relative to hydroxyurea use. Discussion In a LMIC hematology-specialized center, VOCs accounted for most acute visits from patients with SCD, but costs were highest due to anemia exacerbation. Analgesics, antibiotics, and housing drove most expenses. Hydroxyurea may reduce ED costs among individuals with HbSS/HbSβ0-thalassemia but is dependent on adherence level.